Employee Digital Wellness and Work Engagement in Hybrid Work Settings: the Moderating Role of Organizational Support for Wellbeing - Riski Eko Ardianto; Abdi Fadhlan; Ismamudi Ismamudi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to examine the effect of Employee Digital Wellness (EDW) on Work Engagement (WE) among administration and digital marketing employees in startup companies implementing hybrid working, and to explore the moderating role of Organizational Support for Wellbeing (OSW). Using a quantitative approach, data were collected through a 5-point Likert scale questionnaire from 160 purposive-sampled respondents. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.1.1.7. The findings indicate that EDW positively and significantly affects WE (β=0.621; t=8.943; p<0.001), confirming that employees who manage digital technology usage effectively tend to be more energetic, dedicated, and fully engaged in their work. In addition, OSW also positively influences WE (β=0.412; t=5.672; p<0.001), demonstrating that tangible organizational support in the form of wellbeing policies, flexible work arrangements, and mental health programs enhances work engagement. Moreover, OSW moderates the EDW → WE relationship (β=0.173; t=2.713; p=0.007), indicating that the positive effect of digital wellness on engagement is stronger when organizational support is sufficient. These findings highlight the importance of both personal management of digital wellness and consistent organizational wellbeing policies. Practically, organizations are advised to provide digital wellbeing programs, flexible working arrangements, and managerial support to maximize employee engagement, particularly in hybrid working contexts.